PEMANFAATAN LABU KUNING DAN DAUN PEPAYA SEBAGAI PRODUK UNGGULAN DESA SELOBANTENG SITUBONDO - Danang Pramudya Permadi; Farah Sekarwangi Salsabila; Anindya Yola Ilmi; Cindy Puteri Anggraeni; Dinda Sintia Putri; Mitha Devaris Dewi Anjani; Dias Rizky Juli Andika Putra; Meiryka Franola Br Sembiring; Safirul Maarif; Bintang Waidilah Ata Qurba; Mirza Dwi Putri Afkaria; Fiska Maulidian Nugroho (Anfa Mediatama, 2023)
Selobanteng which is also known as Loros is a village located in District of Banyuglugur, Regency of Situbondo, East Java. Stunting is a significant issue in the village of Selobanteng. Another issue is that the village's arid environment makes it difficult for vegetation to thrive. As a result, we, as a group of Student Community Service 103 from Jember University, innovated by creating two items to address those issues. The two items that we're referring to are Yellow Pumpkin Jelly Milk and Vegetable Pesticides of Papaya Leaves.